Australia in the US Empire A Study in Political Realism - Paul, Erik (Springer International Publishing, 2018)
This book argues that Australia is vital to the US imperial project for global hegemony in the struggle among great powers, and why Australia's deep dependency on the US is incompatible with democracy and the security of the country. The Australian continent is increasingly a contestable geopolitical asset for the US grand strategy and for China's economic and political expansionism. The election of Donald Trump to the US presidency is symptomatic of the US hegemonic crisis. The US is Australia's dangerous ally and the US crisis is a call for Australia to regain sovereignty and sever its military alliance with the US. Political realism provides a critical paradigm to analyse the interactions between capitalism, imperialism and militarism as they undermine Australian democracy and shift governmentality towards new forms of authoritarianism. Erik Paul is at the University of Sydney in the Department of Peace and Conflict Studies. He was the last president of the University of Sydney's Centre for Peace and Conflict Studies. Erik is a highly experienced lecturer and much-published researcher specialising in Australia's relations with the Asia-Pacific and the US and issues of regional and world peace. His latest book is Australian Political Economy of Violence and Non-Violence (2016).